2019
DOI: 10.1088/1361-6528/ab3697
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous temperature dependent thermal conductivity of two-dimensional silicon carbide

Abstract: Recently, two-dimensional silicon carbide (2D-SiC) has attracted considerable interest due to its exotic electronic and optical properties. Here, we explore the thermal properties of 2D-SiC using reverse non-equilibrium molecular dynamics simulation. At room temperature, a thermal conductivity of ∼313 W mK −1 is obtained for 2D-SiC which is one order higher than that of silicene. Above room temperature, the thermal conductivity deviates the normal 1/T law and shows an anomalous slowly decreasing behavior. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 72 publications
(116 reference statements)
9
41
0
Order By: Relevance
“…From the extrapolation value when 1 /L → 0, we can determine intrinsic thermal conductivity values under different environmental temperatures, as shown in Fig. 10 e. In general, the higher the ambient temperature increases, the more κ is reduced, which is consistent with previous studies 54 , 55 . In addition, the results showed that κ in the zigzag direction is lower than κ in the armchair direction.…”
Section: Resultssupporting
confidence: 86%
“…From the extrapolation value when 1 /L → 0, we can determine intrinsic thermal conductivity values under different environmental temperatures, as shown in Fig. 10 e. In general, the higher the ambient temperature increases, the more κ is reduced, which is consistent with previous studies 54 , 55 . In addition, the results showed that κ in the zigzag direction is lower than κ in the armchair direction.…”
Section: Resultssupporting
confidence: 86%
“…Consequently, the estimated thermal conductivities for 100 × 10.8 nm 2 graphene ( k G ) , 2D-SiC (4) www.nature.com/scientificreports/ ( k 2D−SiC ) and the heterostructure ( k G/2d−SiC ) are 812.2113 W/m-K, 145.177 W/m-K, and 451.616 W/m-K, respectively. The obtained thermal conductivities of graphene and 2D-SiC are in line with former literature 1,23,44 . Moreover, the calculated thermal conductivity of the graphene/2D-SiC heterobilayer shows a quite high value compared to the thermal conductivities of graphene/MoS 2 45 , graphene/MoSe 2 46 , graphene/stanene 41 , silicene/ graphene 16 and individual 2D-SiC 23 of the same length.…”
Section: Resultssupporting
confidence: 91%
“…A linear drop of temperature can be perceived from the hot area to the cold area. Earlier RNEMD simulations also reported 23,24,[42][43][44] similar phenomena for various heterobilayers as well as 2D material systems. The thermal conductivity was calculated by taking the temperature gradient, which was obtained from linear fitting.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations